2022
DOI: 10.1039/d1fo04428a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prebiotic fructooligosaccharides on gut dysbiosis and inflammation in obesity and diabetes related kidney disease

Abstract: Obesity is an extensive health problem worldwide that is frequently associated with diabetes. It is a risk factor for the development of several diseases including diabetic nephropathy. Recent studies have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that synbiotics, a combination of probiotics and prebiotics, exhibit a more potent effect than probiotics or prebiotics alone, and that multi-strain probiotics are more effective and consistent than single-strain probiotics [30,31]. The literature recommends a minimum daily dosage of 106 CFU for multi-strain probiotics and 1-4 g of fructooligosaccharides (FOS) for prebiotics for a minimum of 10 weeks to effectively reduce gut dysbiosis and inflammation in patients with obesity and diabetes-related kidney disease [32]. Several studies have also supported the anti-obesity effects of certain bacterial strains, such as Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that synbiotics, a combination of probiotics and prebiotics, exhibit a more potent effect than probiotics or prebiotics alone, and that multi-strain probiotics are more effective and consistent than single-strain probiotics [30,31]. The literature recommends a minimum daily dosage of 106 CFU for multi-strain probiotics and 1-4 g of fructooligosaccharides (FOS) for prebiotics for a minimum of 10 weeks to effectively reduce gut dysbiosis and inflammation in patients with obesity and diabetes-related kidney disease [32]. Several studies have also supported the anti-obesity effects of certain bacterial strains, such as Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics such as FOS have been shown to increase butyrate production and promote growth of butyrate-producing bacteria such as Bifidobacterium pseudolongum Lactobacillus, Coprococcus , and Enterococcus [ 126 ]. Recent studies have also shown their potential to reduce serum and total levels of uremic toxins such as p-cresyl sulfate in non-diabetic CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fructooligosaccharide (FOS) is a common prebiotic. FOS supplementation can improve the renal-related pathological changes caused by diabetes ( Pengrattanachot et al., 2022 ). Similarly, FOS has a protective effect on the kidneys of rats with STZ-induced type 1 diabetes mellitus (T1DM) and improves diabetes-related metabolic abnormalities ( Gobinath et al., 2010 ).…”
Section: Gut Microbiota and Microbial Metabolites As Therapeutic Stra...mentioning
confidence: 99%